Investigation And Analysis Of Higher Education Polytechnical Institute Activities According To Typological Series. - V. Babenko; T. Babina; O. Gabzovska; A. Savitsky (Kherson State University, 2009)
In article results of higher education institutes activities lines investigation and analysis are presented. Under investigation there were state ownership higher education institutes and private property higher education institutes. Especially, higher education polytechnical institutes were investigated. Higher education polytechnical institutes features are defined, tasks and functions were summarized. According typological series, higher education polytechnical institutes activities categories are defined.